2007
DOI: 10.1002/pmic.200700745
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of vitreous proteomes from proliferative diabetic retinopathy and nondiabetic patients

Abstract: Diabetes can lead to serious microvascular complications like proliferative diabetic retinopathy (PDR), which is the leading cause of blindness in adults. The proteomic changes that occur during PDR cannot be measured in the human retina for ethical reasons, but could be reflected by proteomic changes in vitreous humor. Thus, we considered that comparisons between the proteome profiles of the vitreous humors of PDR and nondiabetic controls could lead to the discovery of novel pathogenic proteins and clinical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(137 citation statements)
references
References 52 publications
2
133
1
1
Order By: Relevance
“…Carbonic anhydrase (CA) has been identified by proteomic analysis in the vitreous humour from PDR patients; CA production was increased in the vitreous of diabetic retinopathy patients compared with the controls [7,8]. In this study, we have confirmed this finding.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Carbonic anhydrase (CA) has been identified by proteomic analysis in the vitreous humour from PDR patients; CA production was increased in the vitreous of diabetic retinopathy patients compared with the controls [7,8]. In this study, we have confirmed this finding.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have identified some proteins that are differentially expressed in the vitreous of PDR patients. Many of the proteins are involved in such processes as angiogenesis, cellular proliferation, acute phase response, vascular permeability changes, and oxygen-induced vessel loss [7,13]. These studies involved the use of vitreous from non-diabetic patients with macular hole (MH) or macular epiretinal membrane (MEM) as control groups.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry (MS)‐based quantitative proteomics provides a means for the determination of global proteome changes at the tissue and cellular levels, enabling a molecular level characterization of the pathophysiologies of complex eye disorders. Currently, most proteomic studies characterizing disease‐induced vitreous proteome changes have focused on proliferative and nonproliferative diabetic retinopathies (Kim et al, 2007; Loukovaara et al, 2015; Wang, Feng, Hu, Xie, & Wang, 2013), proliferative vitreoretinopathy (Garweg, Tappeneiner, & Halberstadt, 2013; Mitry, Fleck, Wright, Campbell, & Charteris, 2010), and age‐related macular degeneration (AMD; Koss et al, 2014), whereas iERM and MH remain less‐studied (Mandal et al, 2013; Pollreisz et al, 2013; Yu et al, 2014; Zhang et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…5 A recent study using pooled vitreous samples and protein identification based on at least one peptide match has further expanded the list of vitreous proteins. 13 In this report, we have expanded the number of independent vitreous samples analyzed and have compiled and compared results generated from X!Tandem and SEQUEST algorithms. This analysis resulted in the identification of 252 proteins, which was based on at least 2 unique peptide matches and confirmation in independent vitreous samples.…”
Section: Introductionmentioning
confidence: 99%